x3 - 8 - (x - 2).(x - 12) = 0
<=> x3 - 23 - (x - 2).(x - 12) = 0
<=> (x - 2).(x2 + 2x + 4) - (x - 2).(x - 12) = 0
<=> (x - 2).(x2 + 2x + 4 - x + 12) = 0
<=> (x - 2).(x2 + x + 16) = 0
<=> x - 2 = 0
<=> x = 2
Vậy: x = 2
x3 - 8 - ( x - 2 )( x - 12 ) = 0
⇔ ( x - 2 )( x2 + 2x + 4 ) - ( x - 2 )( x - 12 ) = 0
⇔ ( x - 2 )( x2 + 2x + 4 - x + 12 ) = 0
⇔ ( x - 2 )( x2 + x + 16 ) = 0
⇔ x - 2 = 0 hoặc x2 + x + 16 = 0
⇔ x = 2 < do x2 + x + 16 = ( x2 + x + 1/4 ) + 63/4 = ( x + 1/2 )2 + 63/4 ≥ 63/4 > 0 ∀ x >
\(x^3-8-\left(x-2\right)\left(x-12\right)=0\)
\(\Leftrightarrow\left(x-2\right)\left(x^2+2x+4\right)-\left(x-2\right)\left(x-12\right)=0\)
\(\Leftrightarrow\left(x-2\right)\left(x^2+x+16\right)=0\)
\(\Leftrightarrow x-2=0\) ( vì \(x^2+x+16>0\forall x\) )
\(\Leftrightarrow x=2\)
vậy.......